Serotyping of pneumococci: evaluation of the genetic approach and performance with clinical samples - Burckhardt, Irene; Zimmermann, Stefan (Diagnostic microbiology and infectious disease, 2014)
Determination of pneumococcal serotypes depends on a successful culture and the Quellung's reaction. However, in 2006, the capsular sequences of 90 different pneumococcal capsular loci were published, thus making “genetic” serotyping via PCR possible. We wanted to determine the reliability of the published primers for the 13 serotypes included in pneumococcal conjugated vaccine 13 (PCV13) with pneumococcal isolates from Germany. We used a multiplex PCR approach and agarose gel detection of amplicons. Three hundred ninety well-characterized strains of Streptococcus pneumoniae and 46 clinical samples were used in the study. A 100% concordance was achieved between PCR and Quellung's reaction. In 7 clinical samples with a PCR positive for S. pneumoniae, we could determine a serotype included in PCV13.